Detecting Latency Degradation Patterns in Service-based Systems - Cortellessa, Vittorio; Traini, Luca (arXiv.org, 2020)
Performance in heterogeneous service-based systems shows non-determistic trends. Even for the same request type, latency may vary from one request to another. These variations can occur due to several reasons on different levels of the software stack: operating system, network, software libraries, application code or others. Furthermore, a request may involve several Remote Procedure Calls (RPC), where each call can be subject to performance variation. Performance analysts inspect distributed traces and seek for recurrent patterns in trace attributes, such as RPCs execution time, in order to cluster traces in which variations may be induced by the same cause. Clustering "similar" traces is a prerequisite for effective performance debugging. Given the scale of the problem, such activity can be tedious and expensive. In this paper, we present an automated approach that detects relevant RPCs execution time patterns associated to request latency degradation, i.e. latency degradation patterns. The presented approach is based on a genetic search algorithm driven by an information retrieval relevance metric and an optimized fitness evaluation. Each latency degradation pattern identifies a cluster of requests subject to latency degradation with similar patterns in RPCs execution time. We show on a microservice-based application case study that the proposed approach can effectively detect clusters identified by artificially injected latency degradation patterns. Experimental results show that our approach outperforms in terms of F-score a state-of-art approach for latency profile analysis and widely popular machine learning clustering algorithms. We also show how our approach can be easily extended to trace attributes other than RPC execution time (e.g. HTTP headers, execution node, etc.).